Асимптотична поведінка цілих функій з винятковими значениями у співідношенні Бореля - Филевич, П.В. (Український математичний журнал, 2001)
Hexaй Mf(r) i μf(r) — відповідно максимум модуля i максимальний член цілої функції f, а l(r) — неперервно диференційовна i опукла відносно lnr фупкція. Встановлено, що для того щоб lnMf(r)∼lnμf(r),r→+∞ — для кожпої цілої функції f такої, що μf(r)∼l(r),r→+∞, необхідно i досить, щоб ln(rl'(r))=o(l(r)),r→+∞. Let Mf(r) and μf(r) be, respectively, the maximum of the modulus and the maximum term of an entire function f and let l(r) be a continuously differentiable function convex with respect to ln r. We establish that, in order that ln Mf(r) ∼ lnμf(r), r → +∞, for every entire function f such that μf(r) ∼ l(r), r → +∞, it is necessary and sufficient that ln(rl′(r)) = o(l(r)), r → +∞.